Role of Glycans in Cancer Cells Undergoing Epithelial–Mesenchymal Transition - Li, Xiang; Wang, Xin; Tan, Zengqi; Chen, Si; Guan, Feng (Frontiers in Oncology, 2016)
The term “cancer” refers to a group of diseases involving abnormal cell growth with the potential to invade or spread to other parts of the body. Epithelial–mesenchymal transition (EMT), a process whereby epithelial cells lose their cell polarity and cell–cell adhesion ability, and acquire migratory and invasive properties to gain mesenchymal phenotype, is an important step leading to tumor metastasis. Glycans, such as N-glycans, O-glycans, and glycosphingolipids, are involved in numerous biological processes, including inflammation, virus/bacteria–host interactions, cell–cell interactions, morphogenesis, and cancer development and progression. Aberrant expression of glycans has been observed in several EMT models, and the functional roles of such glycans in cancer development and progression has been investigated. We summarize here recent research progress regarding the functions of glycans in cancer cells undergoing EMT. Better understanding of the mechanisms underlying aberrant glycan patterns in EMT and cancer will facilitate the development of such glycans as cancer biomarkers or as targets in design and synthesis of anti-tumor drugs.